Prioritizing Functional Capacity as a Principal End Point for Therapies Oriented to Older Adults With Cardiovascular Disease: A Scientific Statement for Healthcare Professionals From the American Heart Association. Issue 16 (18th April 2017) - Forman, Daniel E.; Arena, Ross; Boxer, Rebecca; Dolansky, Mary A.; Eng, Janice J.; Fleg, Jerome L.; Haykowsky, Mark; Jahangir, Arshad; Kaminsky, Leonard A.; Kitzman, Dalane W.; Lewis, Eldrin F.; Myers, Jonathan; et al.
Abstract : Adults are living longer, and cardiovascular disease is endemic in the growing population of older adults who are surviving into old age. Functional capacity is a key metric in this population, both for the perspective it provides on aggregate health and as a vital goal of care. Whereas cardiorespiratory function has long been applied by cardiologists as a measure of function that depended primarily on cardiac physiology, multiple other factors also contribute, usually with increasing bearing as age advances. Comorbidity, inflammation, mitochondrial metabolism, cognition, balance, and sleep are among the constellation of factors that bear on cardiorespiratory function and that become intricately entwined with cardiovascular health in old age. This statement reviews the essential physiology underlying functional capacity on systemic, organ, and cellular levels, as well as critical clinical skills to measure multiple realms of function (eg, aerobic, strength, balance, and even cognition) that are particularly relevant for older patients. Clinical therapeutic perspectives and patient perspectives are enumerated to clarify challenges and opportunities across the caregiving spectrum, including patients who are hospitalized, those managed in routine office settings, and those in skilled nursing facilities. Overall, this scientific statement provides practical recommendations and vital conceptual insights.